STRATEGI GURU DALAM PENANAMAN AKHLAKUL KARIMAH SISWA DI MADRASAH ALIYAH TARBIYATUL ISLAM SOKO TUBAN - Nasucha, Andi Alfian; Muizuddin, M. (LPPM STAI Al-Azhary Cianjur, 2025)
The cultivation of akhlakul karimah (noble character) in students is a crucial aspect of shaping individuals with integrity and moral excellence. Teachers, as the primary agents of education, play a strategic role in instilling moral values and virtuous character within the school environment. This study aims to describe the strategies employed by teachers in fostering akhlakul karimah among students, as well as to identify the supporting and inhibiting factors encountered during implementation. A descriptive qualitative approach was applied, with data gathered through observations, interviews, and documentation. The findings reveal that teachers implement various strategies, including role modeling, habituation, moral advice (mau’izhah), the integration of moral values into instruction, as well as persuasive and dialogical techniques. Factors supporting the process include a conducive school environment and parental involvement, while inhibiting factors consist of students’ lack of awareness and negative external influences. In conclusion, the successful cultivation of akhlakul karimah depends significantly on the consistency of teachers’ strategies and the synergy established among schools, families, and the broader community.